The Effect of Benefits and Ease of Mobile Banking in Building Customer Loyalty Among BRImo Users in Palakka Village, Kahu District, Bone Regency - Hasriani; Ismail Keri; Rahma Hidayati Darwis (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
Benefit is defined as a measure whereby the use of a technology is believed to bring benefits to the person using it, and perceived ease of use is also defined as the extent to which a person believes that using a technology will be free from effort. This construct is also a belief about the decision-making process. In this case, the researcher intends to examine the effect of the benefits and ease of mobile banking in building customer loyalty among BRImo users in Palakka Village, Kahu District, Bone Regency. This research approach uses a quantitative approach with field research type and conducts observation first, then provides questionnaires in the form of questions through online means, namely Google Form, with 100 samples according to the required data, and uses multiple linear regression analysis with the help of SPSS application. Then the research data results are analyzed and described to look further into the effect of benefits and ease of use in building customer loyalty among BRImo users. The research results show that the effect of benefits and ease of use significantly and positively influences the building of customer loyalty among BRImo users in Palakka Village, Kahu District, Bone Regency by 83%, and the remaining 17% is influenced by other variables outside the research model.